2013 IEEE Sixth International Conference on Software Testing, Verification and Validation 2013
DOI: 10.1109/icst.2013.45
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Test Fixture Strategies and Smells

Abstract: Designing automated tests is a challenging task. One important concern is how to design test fixtures, i.e. code that initializes and configures the system under test so that it is in an appropriate state for running particular automated tests. Test designers may have to choose between writing in-line fixture code for each test or refactor fixture code so that it can be reused for other tests. Deciding on which approach to use is a balancing act, often trading off maintenance overhead with slow test execution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(91 citation statements)
references
References 12 publications
2
87
0
2
Order By: Relevance
“…Unlike other existing detection tools (e.g., [35] or [36]), this tool can identify all the test smells considered in this study. Basically, the tool relies on the detection rules described in Table II.…”
Section: B Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other existing detection tools (e.g., [35] or [36]), this tool can identify all the test smells considered in this study. Basically, the tool relies on the detection rules described in Table II.…”
Section: B Data Extractionmentioning
confidence: 99%
“…Later on, Meszaros defined other smells affecting test code [29]. Based on these catalogs, Greiler et al [35], [62] showed that test smells affecting test fixtures frequently occur in industrial contexts, and for this reason they presented TESTHOUND, a tool able to identify fixturerelated test smells such as General Fixture or Vague Header Setup [35]. Van Rompaey et al [36] devised a heuristic code metric-based technique able to identify instances of two test smells, i.e., General Fixture and Eager Test, but the results of an empirical study showed the low accuracy of the approach.…”
Section: A About Test Smellsmentioning
confidence: 99%
“…Otherwise, they end up with poor solutions to recurring implementation and design problems in their test code, also known as test smells [6]. To support developers during the analysis and adjustment of test fixtures, we previously developed a tool called TestHound 2 to automatically detect test fixture smells and guide test code refactoring [7].…”
Section: Introductionmentioning
confidence: 99%
“…Garousi et al [43] highlights that around half of primary studies investigated test smells, whereas other studies used coverage as an indicator of test code/ assertions quality. Some studies on test smells argue that these issues degrade the quality of test code since test smells prevent the maintainability of test codes written by the development teams [20,35]. Madeyski [26] on the other hand discusses the quality of test suite in terms of their thoroughness and effectiveness: Coverage metrics are indicators of test suite thoroughness, while mutation score indicator is found to be effective at finding faults [26].…”
Section: Unit Testingmentioning
confidence: 99%
“…Studies on test smells often propose new test smell sub-categories such as general fixture and eager, and methods to detect those (e.g. [20], [35]), or they study the impact of test smells on maintenance activities (e.g. [32]).…”
Section: Test Smellsmentioning
confidence: 99%